Powdered siling labuyo (Capsica Frustesceus Linn. Fru) by combination solar and dendrothermal drying - Deloso, Zarmi P.
A procedure for chili powder production was developed using the "siling labuyo" (Capsicum frutescens (Linn.) Fruw.) as raw material. The chili pods were subjected to different pre-treatment methods prior to dehydration: roasting, blanching and lye peeling. Another batch of chilis was dehydrated without any pre-treatment. It was shown that there were no significant differences among the pre-treated chilis dehydrated at the same temperature. All the chilis of different pre-treatment methods were dehydrated in a cabinet dryer using three different temperatures: 55°C, 65°C and 75°C. The best drying temperature was at 65°C because chilis dehydrated at 75°C had slight burnt taste while those dried at 55°C took a long time to dry. A five-kilogram untreated chili was dehydrated using the combination solar and dendrothermal dryer at 65°C. this was also powdered and evaluated. It was shown to have the same quality as the chili dehydrated in the cabinet dryer at 65°C.